2017
DOI: 10.1177/0095399717700224
|View full text |Cite
|
Sign up to set email alerts
|

Welfare State Regimes and Caseworkers’ Problem Explanation

Abstract: In frontline bureaucracy research, the dominant view holds that frontline workers resist managerial pressure to “blame the poor” by bending the rules based on moral considerations, a practice labeled “citizen agency.” We suggest that frontline responses to managerial pressure are filtered through welfare state regime type. Based on in-depth study of caseworker reasoning in Sweden and Denmark, we find a “structural problem explanation” that sees reasons for clients seeking support as rooted in the structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
1
27
0
6
Order By: Relevance
“…Some authors have discussed how new public management reforms changed the size and uses of discretion (Taylor & Kelly, ) because of the reform's impact on management systems (Sowa, Staples, & Zapfel, ; Taylor & Kelly, ), in accountability (Jessens, ) and in ICTs (Raaphorst, Boer, & Bruijn, ; Sowa et al, ). Other authors have shown how cultural and social aspects influence the exercise of discretion (Dubois, ; Maynard‐Moody & Musheno, ; Møller & Stensota, ; Stone, ). This is because bureaucrats' social histories play an essential role in the construction of their habits (Harrits & Møller, ), so the way bureaucrats understand citizens influences their decisions (Harrits, ; Møller & Stone, ) and the signals they interpret (Raaphorst & Van de Walle, ).…”
Section: Social Network and Relationships: Approaching Interactive Imentioning
confidence: 99%
“…Some authors have discussed how new public management reforms changed the size and uses of discretion (Taylor & Kelly, ) because of the reform's impact on management systems (Sowa, Staples, & Zapfel, ; Taylor & Kelly, ), in accountability (Jessens, ) and in ICTs (Raaphorst, Boer, & Bruijn, ; Sowa et al, ). Other authors have shown how cultural and social aspects influence the exercise of discretion (Dubois, ; Maynard‐Moody & Musheno, ; Møller & Stensota, ; Stone, ). This is because bureaucrats' social histories play an essential role in the construction of their habits (Harrits & Møller, ), so the way bureaucrats understand citizens influences their decisions (Harrits, ; Møller & Stone, ) and the signals they interpret (Raaphorst & Van de Walle, ).…”
Section: Social Network and Relationships: Approaching Interactive Imentioning
confidence: 99%
“…Her er det de svageste grupper, der bliver de mest sårbare, når det faglige skøn bliver til tjeklister (Ohemeng & Mccall-Thomas 2013). Dette kan fremme rigiditet i det fagprofessionelle skøn og i deres arbejdsgange og føre til uønsket strategisk adfaerd (fx 'creaming') i forsøget på at leve op til de opstillede mål (Møller & Stensöta 2017). Her viser et studie fra reviewet, hvordan velfaerdsprofessionelle demotiveres i mødet med resultatbaseret styring.…”
Section: Ikke-intenderede Konsekvenser Af Resultatbaseret Styringunclassified
“…[Author]'s in-depth study of caseworker reasoning in Sweden and Denmark shows that frontline responses to managerial pressure are filtered through welfare state regime types (Møller, 2017). Finally, Jewell's (2007) study of social assistance in Sweden, Germany and the U.S.A. explores the impact of welfare state types on how the state handles social assistance and services for unemployed people at the street level.…”
Section: Developing Comparative Approaches To Street-level Bureaucracymentioning
confidence: 99%
“…In practice, much research on street-level bureaucrats focusses on roles and role conceptions, accepting the validity of the ways people explain their activities (see, e.g. Møller, 2017;2012), whereas few studies include citizen perspectives or administrative data as a way to validate such insights on public policy delivery (see Soss, Fording, & Schram, 2011 for an exception).…”
Section: Developing a Logic Of Critical Explanation And Functional Comentioning
confidence: 99%